Estudo do padrão da distribuição espaço-temporal dos casos de AIDS por município de Minas Gerais - período entre 2000 e 2010 - Daniela Lima Magalhães (2015)
According to the Brazilian epidemiological bulletin of the national department of STD/AIDS and viral hepatitis, they were recorded by the year 2014, 757 042 aids cases. Around 255,000 do not know their hiv status, which contributes to the spread of the disease. The epidemiological profile of AIDS in Brazil has experienced many changes over the years, an important trend is the incorporation of socially vulnerable populations. This fact is consistent with a country characterized by social inequalities, significant differences in the distribution patterns of income and education as well as access to services and health programs. Despite this context, Brazil stands out on the world stage for the quality of the public health policy of the Ministry of Health to assist PLHA. To achieve this quality, it is essential to systematicly analyse of large volumes of information to support control mechanisms, processes, procedures, and especially the consequent decision making and development of public health policies. This study aimed to examine the incidence of reported aids cases in municipalities of minas gerais from 2000 to 2010, and to investigate the association with demographic, social and economic, including the coverage of the Wage Transfer Programme. This is an ecological study with data from the ibge and the joão pinheiro foundation. Variables were arranged according to the software package minas gerais state index of social responsibility (MGSSRI): healthcare; educational attainment; social assistance and citizenship; income and employment; financial performance; housing and environment; population and area, public security. This study used the bayesian approach to generating temporal and spatio-temporal models. The spatial effect was incorporated using the spatial model of the ICAR type. The final model made it possible to create maps with the relative risk of the municipalities, showing the evolution of the epidemic in the state during the period analyzed. Regarding the association between socioeconomic variables and the number of AIDS cases, an tendency of feminization and countryside spreed of the epidemic was identified. The presence of the space factor has clarified the variables that have similar spatial distribution with the number of aids cases. The evolution of the relative risks associated with AIDS between 2000 and 2010 points to an increase in this risk in most municipalities. Before the great social, economic and demographic differences in a diverse state such as Minas Gerais, the AIDS epidemic presents with divence profiles influenced by the peculiarities of each municipality.